Structural, magnetic and transport properties of magnetoelectric composites - Rahman, M. Azizar; Gafur, M.A.; Hossain, A.K.M. Akther (Journal of magnetism and magnetic materials, 2013)
Magnetoelectric composites of nominal chemical compositions (y)Mn0.45Ni0.05Zn0.50Fe2O4+(1-y)BaZr0.52Ti0.48O3 (where y varies from 0 to 1.0 in steps of 0.20) were prepared by the standard solid state reaction technique. The samples were sintered at various temperatures. X-ray diffraction patterns confirm the presence of the constituent phases. The initial permeability increases with increasing ferrite content and also with increasing sintering temperature. However, there is a slight decrease in initial permeability value for samples sintered above 1573 K. The dielectric dispersion is observed at lower frequencies (<103 Hz) due to interfacial polarization. The dielectric constant is almost independent at high frequencies (>104 Hz) for a particular composition because of the inability of electric dipoles to follow the fast variation of the alternating applied electric field. The ac electrical conductivity increases with increasing frequency, suggesting that the conduction is due to small polaron hopping. The increase in dielectric constant and dielectric loss corresponds to the increase in ac electric conductivity with increasing sintering temperature up to 1573 K. The magnetoelectric voltage coefficient of the composites decreases with increasing ferrite content and dc magnetic field.